PEMBERIAN GANTI RUGI SEBAGAI BENTUK PERLINDUNGAN HUKUM BAGI PASIEN DALAM TINDAK PIDANA DI BIDANG MEDIS - Andika Putra, I Gede; Wiryawan, I Wayan (Kertha Wicara : Journal Ilmu Hukum, 2014)
One of the form of legal protection given to the patient is proposing compensation by the patient who feel aggrieved by the health personnel. The issue that is raised is the legal basic of proposing compensation, type and the mechanism of proposing compensation by the patient. The purpose of this paper is to acknowledge and understand the compensation which is given as a form of legal protection for victim of the crime in medical field. The method which is used is the normative research method due to the vagueness of norms towards the regulation of compensation in Act Number 23 of 1992 on Health. The legal basic used by the patient to demand compensation to the doctor or health facility is Act Number 23 of 1992 Article 55 paragraph (1) and paragraph (2). By not strictly regulated or even not refer in detail about the compensation provisions of the Health Law, the judge has the power to apply the compensation in accordance with the principles of propriety. While the submission of compensation under the provisions of Article 98 to Article 100 of Act Number 8 of 1981 on Criminal Proceedings in the form of compensation to victim of malpractice in criminal justice which can be done by the judge through the incorporation of criminal cases with civil tort cases.
Keywords: Compensation, Legal Protection, Criminal Act, Medic